Hubungan antara kesedaran metakognisi, motivasi dan pencapaian akademik pelajar universiti - Saemah Rahman, -; John Arul Philips, - (2006)
Review of literature showed the importance of metacognition and motivation on students learning. However, research incorporating both factors in Malaysia is still scarce. This study was conducted to examine the relationship between metacognition, motivation, and academic achievement among university students. The sample consisted of 374 Second Year university students drawn